Single-nucleus and spatial landscape of the sub-ventricular zone in human glioblastoma - Yamhilette Licón-Muñoz; Vanessa Avalos; Suganya Subramanian; Bryan Granger; Frank Martinez; Leopoldo A. García-Montaño; Samantha Varela; Drew Moore; Eddie Perkins; Michael Kogan; Stefano Berto; Muhammad O. Chohan; et al. (Cell Reports)
Summary: The sub-ventricular zone (SVZ) is the most well-characterized neurogenic area in the mammalian brain. We previously showed that in 65% of patients with glioblastoma (GBM), the SVZ is a reservoir of cancer stem-like cells that contribute to treatment resistance and the emergence of recurrence. Here, we build a single-nucleus RNA-sequencing-based microenvironment landscape of the tumor mass and the SVZ of 15 patients and two histologically normal SVZ samples as controls. We identify a ZEB1-centered mesenchymal signature in the tumor cells of the SVZ. Moreover, the SVZ microenvironment is characterized by tumor-supportive microglia, which spatially coexist and establish crosstalks with tumor cells. Last, differential gene expression analyses, predictions of ligand-receptor and incoming/outgoing interactions, and functional assays reveal that the interleukin (IL)-1β/IL-1RAcP and Wnt-5a/Frizzled-3 pathways represent potential therapeutic targets in the SVZ. Our data provide insights into the biology of the SVZ in patients with GBM and identify potential targets of this microenvironment.